PENGARUH PEMANASAN ELEKTRODA LAS PADA SUHU 80-120ÂºC TERHADAP SIFAT MEKANIK - ., Zulfah; Wibowo, Agus; Aji, Cusanto Aji (Universitas Pancasakti Tegal, 2011)
This Research purpose to know : (1) Nature of mechanic to influence of warm-up of electrode las (2) Require to do of further research by adding the further variation that is examination Penetran and Radiografi (3) Menetahui hardness of result pengelasan after electrode in heating with selected heat.Pursuant to hypothesis test that writer only using the steel type to in ujikan that is type become militant ST 41 by using electrode las type RD 260 with diameter of 4,0 x 350 mm. Examination result show the existence of the influence signifikan [among/between] electrodes which have through warm-up process and the electrode tampa through warm-up, specially for interesting examination, impack or beat, and examination of hardness where in each;every examination of writer do 3 spesiment in each;every his examination.Way obtain;get the data by using temperature grader [at] industrial kitchen [of] electrics ( Heater Elektroda Las) that is to know the hardness storey;level found on electrode membrane las specially type RD 260 with electrode diameter of 4,0-350mm.Influence of warm-up of electrode las [at] temperature of 80-120°C to nature of mechanic done [by] during 15-30 minute in kitchen induce the electrics [so that/ to be] obtaining the maximal result. used machine for interesting examination is machine test the type Shimadzu UH 1000 kNI, for examination beat [is] to the type test : Hang Ta, HT-8941, is while examination of hardness of writer use the machine test the type : A ffri 206 RT.Keywords: Nature of mechanic to of warm up of elektroda